2005
DOI: 10.1063/1.2009808
|View full text |Cite
|
Sign up to set email alerts
|

Influence of parasitic phases on the properties of BiFeO3 epitaxial thin films

Abstract: We have explored the influence of deposition pressure and temperature on the growth of BiFeO 3 thin films by pulsed laser deposition onto (001)-oriented SrTiO 3 substrates. Singlephase BiFeO 3 films are obtained in a region close to 10 -2 mbar and 580°C. In non-optimal conditions, X-ray diffraction reveals the presence of Fe oxides or of Bi 2 O 3 . We address the influence of these parasitic phases on the magnetic and electrical properties of the films and show that films with Fe 2 O 3 systematically exhibit a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
191
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 380 publications
(210 citation statements)
references
References 16 publications
14
191
2
3
Order By: Relevance
“…High magnetic fields of ∼20 T stabilize the canted antiferromagnetic (CAFM) phase as opposed to the cycloidal phase [13][14][15][16][17]. Although several groups succeeded in realizing the CAFM phase at zero field [18][19][20][21][22][23], the ME effect in this phase has not been clarified. In this study, several features were observed when a magnetic field was applied normal to the trigonal c-axis, and they indicated that a third magnetic phase emerged in bulk BiFeO 3 between the cycloidal and CAFM phases at approximately room temperature.…”
mentioning
confidence: 99%
“…High magnetic fields of ∼20 T stabilize the canted antiferromagnetic (CAFM) phase as opposed to the cycloidal phase [13][14][15][16][17]. Although several groups succeeded in realizing the CAFM phase at zero field [18][19][20][21][22][23], the ME effect in this phase has not been clarified. In this study, several features were observed when a magnetic field was applied normal to the trigonal c-axis, and they indicated that a third magnetic phase emerged in bulk BiFeO 3 between the cycloidal and CAFM phases at approximately room temperature.…”
mentioning
confidence: 99%
“…The thin films of BFO were grown by pulsed laser deposition on SrTiO 3 with a conductive buffer layer of La; Sr MnO 3 [16], and the ferroelectric domain morphology was studied by way of piezo-response atomic force microscopy (PFM). The shape of the spontaneous domains is highly irregular (Fig.…”
mentioning
confidence: 99%
“…The loops are normalised to the saturation. Samples BFO4 and BFO6 display a very weak magnetic moment (reflected in the more noisy signal), that can be attributed to uncompensated moments of the BFO sublattices due to canted spins arising from the Dzyaloshinskii-Moriya interaction [3,4] or the the presence of a parasitic Fe 2 O 3 phase [11]. Conversely, sample BFO5 has a much stronger magnetic moment, that is the sum of a similar contribution coming from the BFO layer and of the magnetisation of the γ-Fe 2 O 3 platelets.…”
Section: Discussionmentioning
confidence: 99%